(untitled) (Journal of the College of Basic Education, 2023)
In this research, the a-2 ratio method and the Tensor Statistical Constant (CST) method were used. to calculate Lineage confusion for transitions kama between levels energy to peer 30 Cu 59 29 generated Who interaction nuclear 30 Cu 59 29 ) (p, 30 Ni 58 28 and for 28 Move Cami And for the first once Where I confirmed results The results obtained showed the validity of this method in calculating mixing ratios and its ability to predict There is no error in the experimental measurements. The results were compared with the available experimental values, and they were in agreement very well in most of them. Some values of mixing ratios that were calculated in this way were acceptable within the range of measurements. The process is like the cam transmission  3  1  with energy (5970 keV).  2 2 